Serum biomarkers of habitual coffee consumption may provide insight into the mechanism underlying the association between coffee consumption and colorectal cancer. Issue 5 (11th March 2015) - Guertin, Kristin A; Loftfield, Erikka; Boca, Simina M; Sampson, Joshua N; Moore, Steven C; Xiao, Qian; Huang, Wen-Yi; Xiong, Xiaoqin; Freedman, Neal D; Cross, Amanda J; Sinha, Rashmi
ABSTRACT: Background: Coffee intake may be inversely associated with colorectal cancer; however, previous studies have been inconsistent. Serum coffee metabolites are integrated exposure measures that may clarify associations with cancer and elucidate underlying mechanisms. Objectives: Our aims were 2-fold as follows: 1 ) to identify serum metabolites associated with coffee intake and 2 ) to examine these metabolites in relation to colorectal cancer. Design: In a nested case-control study of 251 colorectal cancer cases and 247 matched control subjects from the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial, we conducted untargeted metabolomics analyses of baseline serum by using ultrahigh-performance liquid-phase chromatography–tandem mass spectrometry and gas chromatography–mass spectrometry. Usual coffee intake was self-reported in a food-frequency questionnaire. We used partial Pearson correlations and linear regression to identify serum metabolites associated with coffee intake and conditional logistic regression to evaluate associations between coffee metabolites and colorectal cancer. Results: After Bonferroni correction for multiple comparisons ( P = 0.05 ÷ 657 metabolites), 29 serum metabolites were positively correlated with coffee intake (partial correlation coefficients: 0.18–0.61; P < 7.61 × 10 −5 ); serum metabolites most highly correlated with coffee intake (partial correlation coefficients >0.40) included trigonelline ( N ′-methylnicotinate), quinate, and 7 unknown metabolites. Of 29 serum metabolites, 8 metabolites were directly related to caffeine metabolism, and 3 of these metabolites, theophylline (OR for 90th compared with 10th percentiles: 0.44; 95% CI: 0.25, 0.79; P -linear trend = 0.006), caffeine (OR for 90th compared with 10th percentiles: 0.56; 95% CI: 0.35, 0.89; P -linear trend = 0.015), and paraxanthine (OR for 90th compared with 10th percentiles: 0.58; 95% CI: 0.36, 0.94; P -linear trend = 0.027), were inversely associated with colorectal cancer. Conclusions: Serum metabolites can distinguish coffee drinkers from nondrinkers; some caffeine-related metabolites were inversely associated with colorectal cancer and should be studied further to clarify the role of coffee in the cause of colorectal cancer. The Prostate, Lung, Colorectal, and Ovarian trial was registered at clinicaltrials.gov as NCT00002540.